A hyperacute immune map of ischaemic stroke patients reveals alterations to circulating innate and adaptive cells. (9th December 2020) - Krishnan, S; O'Boyle, C; Smith, C J; Hulme, S; Allan, S M; Grainger, J R; Lawrence, C B
Summary: Systemic immune changes following ischaemic stroke are associated with increased susceptibility to infection and poor patient outcome due to their role in exacerbating the ischaemic injury and long-term disability. Alterations to the abundance or function of almost all components of the immune system post-stroke have been identified, including lymphocytes, monocytes and granulocytes. However, subsequent infections have often confounded the identification of stroke-specific effects. Global understanding of very early changes to systemic immunity is critical to identify immune targets to improve clinical outcome. To this end, we performed a small, prospective, observational study in stroke patients with immunophenotyping at a hyperacute time point (< 3 h) to explore early changes to circulating immune cells. We report, for the first time, decreased frequencies of type 1 conventional dendritic cells (cDC1), haematopoietic stem and progenitor cells (HSPCs), unswitched memory B cells and terminally differentiated effector memory T cells re-expressing CD45RA (TEMRA). We also observed concomitant alterations to human leucocyte antigen D-related (HLA-DR), CD64 and CD14 expression in distinct myeloid subsets and a rapid activation of CD4 + T cells based on CD69 expression. The CD69 + CD4 + T cell phenotype inversely correlated with stroke severity and was associated with naive and central memory T (TCM) cells. Our findings highlight early changes in both the innate and adaptive immune compartments for further investigation as they could have implications the development of post-stroke infection and poorer patient outcomes. Graphical Abstract: